Dampak Pandemi Terhadap Tingginya Angka Cerai Gugat di Pengadilan Agama Kabupaten Lima Puluh Kota - Ulfa, Mawaddatul; Bunaiya, Mahlil (Hunafa: Jurnal Studia Islamika, 2021)
Recently divorce cases have become increasingly popular and have become popular in the community. Tens of people a day can change their status to become widows/widowers. The Lima Puluh Kota is one of the largest contributors to divorce cases in Indonesia. In addition to the year of pandemic, 2020 is also marked with the year of divorce, because not yet in December the divorce rate in Lima Puluh Kota has reached 951 divorce case that has entered the religious courts. Of the 951 cases submitted 75% of these cases were claimants. This study aims to describe the driving factors for the increase in the divorce rate (divorce is the wife’s initiative) in the religious courts of Lima Puluh Kota with a descriptive qualitative approach with a phenomenological type. Based on this research, it can be concluded that the highest driving factors for divorce are constant arguments and domestic violence. Other factors that influence it are economic problems, being entangled in legal cases/imprisonment, the relatively young age of marriage.